2019
DOI: 10.1155/2019/7180284
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Imine Resveratrol Analog 2-Methoxyl-3,6-Dihydroxyl-IRA Ameliorates Colitis by Activating Protective Nrf2 Pathway and Inhibiting NLRP3 Expression

Abstract: Resveratrol (RSV) is a naturally occurring polyphenol that exhibits pleiotropic health benefits, including anticolitis and colon cancer-protective activity. Recently, we identified the novel imine RSV analog (IRA), 2-methoxyl-3,6-dihydroxyl-IRA 3,4,5,4-tetramethoxystilbene (C33), as a putative activator of nuclear factor erythroid 2-related factor 2 (Nrf2). The present study was designed to evaluate the ability of C33 to activate the Nrf2 signaling pathway and its anticolitis effect in comparison to RSV. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“… Antioxidant Anti-inflammatory [ 44 ] Inflammatory bowel diseases (IBD) C57BL/6 WT and Nrf2 −/− mice (induced by dextran sulfate sodium); Human colon cancer LS174T and Caco2 cells Intraperitoneal injection/ Imine RSV Analog 2-Methoxyl-3,6-Dihydroxyl-IRA (C33); RSV (200 mg/kg) The derivative C33 modified by RSV showed stronger anti-inflammatory effect, and effectively improved IBD by activating Nrf2 signaling pathway in-vivo and in-vitro . Anti-inflammatory [ 45 ] Autoimmune encephalomyelitis (AE) C57BL/6 mice Intraperitoneal injection/ RSV (10 mg/kg; 25 mg/kg; 50 mg/kg) RSV reduced oxidative stress and inflammation in EAE mice to protect the integrity of blood-brain barrier. Antioxidant Anti-inflammatory [ 46 ] Neurodegenerative diseases Alzheimer disease (AD) Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs); Tg2576 Swedish transgenic AD mice Passage 3 hUC-MSCs were cultured in media with 2.5 µM RSV, and intravenously delivered the suspension of hUC-MSCs to AD mice (1×106 cells/ 200μl saline solution) RSV-treated hUC-MSCs showed a significant neuroinflammatory inhibitory effect that inhibited MAPKs, p38, and other signal pathways in AD mice by interacting with astrocytes and microglia.…”
Section: Discussionmentioning
confidence: 99%
“… Antioxidant Anti-inflammatory [ 44 ] Inflammatory bowel diseases (IBD) C57BL/6 WT and Nrf2 −/− mice (induced by dextran sulfate sodium); Human colon cancer LS174T and Caco2 cells Intraperitoneal injection/ Imine RSV Analog 2-Methoxyl-3,6-Dihydroxyl-IRA (C33); RSV (200 mg/kg) The derivative C33 modified by RSV showed stronger anti-inflammatory effect, and effectively improved IBD by activating Nrf2 signaling pathway in-vivo and in-vitro . Anti-inflammatory [ 45 ] Autoimmune encephalomyelitis (AE) C57BL/6 mice Intraperitoneal injection/ RSV (10 mg/kg; 25 mg/kg; 50 mg/kg) RSV reduced oxidative stress and inflammation in EAE mice to protect the integrity of blood-brain barrier. Antioxidant Anti-inflammatory [ 46 ] Neurodegenerative diseases Alzheimer disease (AD) Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs); Tg2576 Swedish transgenic AD mice Passage 3 hUC-MSCs were cultured in media with 2.5 µM RSV, and intravenously delivered the suspension of hUC-MSCs to AD mice (1×106 cells/ 200μl saline solution) RSV-treated hUC-MSCs showed a significant neuroinflammatory inhibitory effect that inhibited MAPKs, p38, and other signal pathways in AD mice by interacting with astrocytes and microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 and its target genes NQO1, Trx1, SOD2 and HO-1, especially NQO1, was elevated by cardamonin, which has the effect to depress NLRP3 inflammasome activation in a mouse model ( 69 ). And upregulation of Nrf2 has been detected after treatment of Resveratrol and Hydrogen sulfide (H 2 S) ( 70 , 71 ). ROS is considered as a second messenger in pro-inflammatory responses.…”
Section: Nlrp3 Inflammasome In Autoimmune Diseasesmentioning
confidence: 99%
“…However, the accumulating data have shown that the major mechanism for the antioxidant activity of resveratrol is related to its effect on the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway. Resveratrol, by activation of the Nrf2 signaling pathway, ameliorates oxidative stress [68] to improve colitis [69], arthritis [63], diabetes [70] and non-alcoholic fatty liver disease [71].…”
Section: Resveratrol In the Treatment Of Cancermentioning
confidence: 99%
“…Obviously, mitochondrial dysfunction is associated with a variety of pathological conditions such as NDs [93], hepatic disorders [69] and so on. This is due to the potential role of mitochondria in the induction of apoptotic cell death.…”
Section: Mitochondria and Cancermentioning
confidence: 99%